A study on legal immunity of lawyers in Malaysia / Nurul Atiqa Suradi, Shafiqah Mohamed and Siti Nur Zalila Kader Mohammad Ghazali - Suradi, Nurul Atiqa; Mohamed, Shafiqah; Mohammad Ghazali, Siti Nur Zalila Kader (2012)
Fundamental to any study of lawyer ethics is an appreciation of the lawyer's role with respect to the client, the professional itself, the state and the public interest generally. The role of lawyer, of course will vary from one legal system to another but some generalities can be drawn. However, with regards to the nature of being lawyers, they are facing the risk of legal action in the form of civil action as in negligence and exposed to any legal suit against them during handling a articular case. This project paper aims to study on the legal immunity of lawyers in Malaysia. This research will examine the provision in Legal Profession Act 1976 whether the act provides any specific provision with regards to the immunity of lawyers from any legal actions especially in negligence. Besides that, there will be a comparative study between decided cases with regards to the immunity of the lawyers in Malaysia and Australia. Thorough examination and analysis would help identifying the answer on why should immunity for the lawyers be granted or not to be granted. To increase the understanding of the actual problem, this study incorporate semi structured interviews. The interviews have been conducted among the judge, lawyer and senior law lecturer. This research reveals that since lawyers are professional, they cannot neglect their duty and no immunity is provided to shield them from being responsible to their own act.